2004
DOI: 10.1892/0891-6640(2004)18<295:haicc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Abscesses in Cats: 14 Cases (1985–2002)

Abstract: In this retrospective study, we describe 14 cats diagnosed with hepatic abscesses. The objective of the study was to report the clinical signs, physical examination findings, clinicopathologic findings, and outcomes in affected cats. These findings were then compared with those previously reported in dogs and humans. Clinical signs were vague and included anorexia, lethargy, and weight loss. Only 23% of cats had fever, whereas 31% were hypothermic. Increases in serum activities of alanine aminotransferase and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 8 publications
2
41
0
2
Order By: Relevance
“…2,3,5,6,8 Clinical signs are similar to those found in other species such as dogs, cats, and humans. 8,9 Clinical pathological findings in horses are often indicative of systemic inflammation and generally include leukocytosis attributable to mature neutrophilia, hypo-or hyperproteinemia, hypoalbuminemia, hyperglobulinemia, hyperfibrinogenemia, and mildly high liver enzyme activity. 2,[4][5][6] Diagnosis of hepatic abscesses in horses can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,6,8 Clinical signs are similar to those found in other species such as dogs, cats, and humans. 8,9 Clinical pathological findings in horses are often indicative of systemic inflammation and generally include leukocytosis attributable to mature neutrophilia, hypo-or hyperproteinemia, hypoalbuminemia, hyperglobulinemia, hyperfibrinogenemia, and mildly high liver enzyme activity. 2,[4][5][6] Diagnosis of hepatic abscesses in horses can be difficult.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports on abscesses in small animals 1,[4][5][6][7][8][9][10] . Farrar et al 5) reported 14 cases of hepatic abscesses in dogs and aerobic bacteria such as Escherichia coli, Klebsiella pneumoniae, Staphylococcus epidermidis and S. intermedius were mainly isolated from them.…”
Section: Discussionmentioning
confidence: 99%
“…Farrar et al 5) reported 14 cases of hepatic abscesses in dogs and aerobic bacteria such as Escherichia coli, Klebsiella pneumoniae, Staphylococcus epidermidis and S. intermedius were mainly isolated from them. Sergeeff et al 10) reported 14 cases of hepatic abscesses in cat as well and they stated that E. coli was the most commonly cultured organisms. Moreover, Murakami et al 9) reported a case of lymph node abscess caused by Actinomyces viscosus in a cat.…”
Section: Discussionmentioning
confidence: 99%
“…45 In human patients most abscesses are bacterial in nature and most commonly affect the right liver lobes. This may be due to its proximity to the biliary tree or the portal anatomy that permits translocation of intestinal flora.…”
Section: Hepatic Abscessmentioning
confidence: 99%
“…Polymicrobial growth was cultured from 66% of the cats, with E. coli most frequently isolated. 45 Feline patients often present with non-specific clinical signs such as anorexia, lethargy and weight loss. Most affected cats were septic and many were hypothermic.…”
Section: Hepatic Abscessmentioning
confidence: 99%